2020
DOI: 10.1111/hsc.12961
|View full text |Cite
|
Sign up to set email alerts
|

Service users' experiences and views of support for decision‐making

Abstract: This article presents the findings from a qualitative, participatory research project which explored how people with intellectual disabilities and/or mental health problems have, or have not been, supported to make their own decisions. The aim of the research is to help inform how supported decision‐making, as required by Article 12 of the UN Convention on the Rights of Persons with Disabilities, can be effectively operationalised. The project provides an overview of experiences of support as well as identifyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 17 publications
3
16
0
Order By: Relevance
“…Compared with consumers' attitudes toward products, the shopping environment plays a larger role in their decision of which shops they should visit [36]. Some researchers have maintained that store shopping affects the customers' expectations and perceptions, and their satisfaction in the end [37].…”
Section: Influence Of Different Shopping Situations On the Relationshmentioning
confidence: 99%
“…Compared with consumers' attitudes toward products, the shopping environment plays a larger role in their decision of which shops they should visit [36]. Some researchers have maintained that store shopping affects the customers' expectations and perceptions, and their satisfaction in the end [37].…”
Section: Influence Of Different Shopping Situations On the Relationshmentioning
confidence: 99%
“…One key objective of this study was to take a look at the key components of supporting and assessing the decision making ability of people with mental health and/or learning disabilities. In order to meet this objective, the data from a larger project which examined the experiences, approaches and preferences of people making decisions with support (Webb, Davidson, Edge et al, 2020) was re-analysed through the four main components of the capacity test. Ethical approval for the study was granted by the School of Social Sciences, Education and Social Work, Queen's University of Belfast.…”
Section: Methodsmentioning
confidence: 99%
“…This is sometimes referred to as the right to legal capacity and it is important to acknowledge that people can and should retain legal capacity, and their other rights, regardless of whether they have the relevant decision making ability or mental capacity. This paper will identify some of the key components of the support and assessment process and forms part of a larger project which examines the experiences, approaches and preferences of people making decisions with support (Webb, Davidson, Edge et al, 2020). This paper provides a more specific exploration of findings that may relate to the assessment of capacity and how that could inform the design, co-design and provision of support.…”
Section: Introductionmentioning
confidence: 99%
“…None of these forms seem to relate directly to formalised care planning. Webb et al (2020) found little interest among users for formalised care planning and underlines instead the need for individualised, ongoing support for users in decision-making. In a study of user involvement about support in daily living for people with mental health problems, found that user involvement was an integral part of the service built on ongoing dialogue between the user and the professional helper.…”
Section: User Involvement and Individual Plansmentioning
confidence: 99%
“…Webb et al. (2020) found little interest among users for formalised care planning and underlines instead the need for individualised, ongoing support for users in decision‐making. In a study of user involvement about support in daily living for people with mental health problems, Matscheck et al.…”
Section: Introductionmentioning
confidence: 99%